2014
DOI: 10.1155/2014/349078
|View full text |Cite
|
Sign up to set email alerts
|

Study on Induction Heating Coil for Uniform Mold Cavity Surface Heating

Abstract: Recently, energy saving is one of the important issues for polymer processing industry. Electromagnetic induction heating has many advantages such as fast heating and low energy consumption. Previous studies using electromagnetic induction heating for rapid tool heating have indicated that the temperature uniformity on a cavity surface is not easy to be achieved. In this paper, two different coils were used for heating uniform 7 mm thick hot work tool steel (JIS SKD61) surface. One is a four-row coil with oppo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 8 publications
0
22
0
Order By: Relevance
“…S. Huang et al [17][18][19][20][21][22] have compared the performance of oil heating versus induction heating and found the latter to give best replication of micro structures. They also noticed that increasing the mold temperature above the phase transition temperature does not significantly improve the replication ability.…”
Section: Introductionmentioning
confidence: 99%
“…S. Huang et al [17][18][19][20][21][22] have compared the performance of oil heating versus induction heating and found the latter to give best replication of micro structures. They also noticed that increasing the mold temperature above the phase transition temperature does not significantly improve the replication ability.…”
Section: Introductionmentioning
confidence: 99%
“…It implies that the more uniform temperature distribution can be achieved at higher target temperature of the hot-plate. 30 Following the same strategy of analysis, the temperature nonuniformity and difference at other target temperature of 140 ℃, 160 ℃, 200 ℃, and 240 ℃ under the same processing conditions at the target temperature of 180 ℃ can be simulated. Furthermore, the corresponding three-dimensional surface temperature color-map of the hot-plate under different target temperatures can found in the supplemental appendix C. These surface color maps may provide a guide to help determination of optimized processing conditions with uniform temperature distribution at the target surface of hot-plate.…”
Section: Discussionmentioning
confidence: 99%
“…While Sung, Y. T. et al, [4] found that by using inductive heating, the standard deviation of temperature can be ranging from 1.44 o C to 25.82 o C. Standard procedure recommended that to get good parts, the mold surface temperature need to be in the range of ± 2.0 o C [2,5]. Uniformity of the temperature in the molding plate is of paramount important since it will affect the dimensional stability of the part produced.…”
Section: Introductionmentioning
confidence: 99%